PENGARUH PERSON ORGANIZATION FIT DAN KARAKTERISTIK INDIVIDU TERHADAP KOMITMEN ORGANISASI PADA KANTOR PELAYANAN PAJAK PRATAMA MANADO - Meilana Rawung; Mieke Roring; Max Siwi (Universitas Sam Ratulangi, 2014)
To increase the commitmen of organiztions, each organization would requirehuman resources potential. Therefore, the organization is done by various meansto find out thefactors that lead to influence on organizational commitment. In this case, there are two factors thathave been observed by researchers, i.e. : Person Organization Fit and The Characteristics of theindividual. This research aims to know the influence of the Person Organization Fit andCharacteristics of organizational commitment. Document obtained in this study are throughinterview with the Organization and dissemnination of the questionnaire on 60 employees, and usesthe approach of analysis Koefesien Multiple Linear Regression and Corelation. The results of thisreseach indicate Person Organization Fit and Characteristics of individuals collectively influenceon organizational commitmen. However, in this study the commitment compared to individualcharacteristics.Keyword : Person Organization Fit, Individual Characteristics, Organizational Commitment